2012
DOI: 10.1007/s00216-011-5673-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation and protein adduct formation of aniline: a liquid chromatography/mass spectrometry study

Abstract: Historically, skin sensitization tests are typically based on in vivo animal tests. However, for substances used in cosmetic products, these tests have to be replaced according to the European Commission regulation no. 1223/2009. Modification of skin proteins by electrophilic chemicals is a key process associated with the induction of skin sensitization. The present study investigates the capabilities of a purely instrumental setup to determine the potential of commonly used non-electrophilic chemicals to caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Using this type of instrument, tetrazepam metabolism has been investigated by comparing in vivo and in vitro methods [18, 19]. Similar EC/LC–MS/MS methods have been developed for many applications including protein adduct formation by thimerosal with human serum albumin and β-lactoglobulin A [20], protein adduct formation of aniline [21], nucleotide oxidative products generation and identification [22], and protein/peptide disulfide bond conformation by tracking electrolytic cleavage [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Using this type of instrument, tetrazepam metabolism has been investigated by comparing in vivo and in vitro methods [18, 19]. Similar EC/LC–MS/MS methods have been developed for many applications including protein adduct formation by thimerosal with human serum albumin and β-lactoglobulin A [20], protein adduct formation of aniline [21], nucleotide oxidative products generation and identification [22], and protein/peptide disulfide bond conformation by tracking electrolytic cleavage [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The potential was ramped from 0 to 2.5 V versus Pd/H2. At around 750 mV, signals for GSH conjugates (monomer +O and dimer) appear with increasing signal intensities [51]. example, 92% of all proteins in yeast contain at least one cysteine moiety [59].…”
Section: Specific Cysteine Tagging With Electrochemically Generated Rmentioning
confidence: 99%
“…Next to pharmaceuticals and pesticides, skin sensitizers were studied in detail [48][49][50][51][52]. The skin-sensitizing process is assumed to be caused by the covalent binding of allergens or their metabolites to proteins present in the skin.…”
Section: Adduct Formation Between Reactive Intermediates and Biomolecmentioning
confidence: 99%
See 1 more Smart Citation
“…Karst's group was concerned with metabolic pathways of skin sensitizers that can be released from cosmetic products such as hair dyes. Both aniline (phenylamine) [24] and p-phenylenediamine (1,4-diaminobenzene) [25,26] were oxidized electrochemically and trapped with various nucleophiles such as peptides or proteins. Tong et al [27] reported a novel approach for indirect quantification of parent drug and its unstable metabolites by complete online coulometric conversion.…”
Section: Drug Metabolismmentioning
confidence: 99%